Study of Fitted and Computed Plots in Magnetized Plasma Sheath - Adhikari, B. R.; Khanal, R. (BMC Journal of Scientific Research, 2022)
Velocity profile of ions at the sheath entrance position with various obliqueness of the magnetic field has been studied. The oscillation amplitude of the velocity decreases as time increases. The mean values of different component of velocity also changes. The computed and fitted values of the vector sum of oscillatory part of x, y and z-component of velocities of the ions are nearly matches. At angle 30°, damping rate of vector sum of oscillatory part of total velocity increases from 1 to 5 mT. On the other hand vector sum of oscillating part of initial velocity is almost equal for magnetic field 1 mT, 3 mT and 5 mT at the same angle.